Utilization of Chicken Bone Waste into Calcium Fertilizer in SMK N 1 Mojosongo Boyolali - Muhammad Fathul Anwar; Agung Setyarini; Yos Wahyu Harinta (Universitas Veteran Bangun Nusantara, 2025)
This community service activity was carried out with the aim of providing an introduction to the utilization of chicken bones waste, targeting Gen Z in this case students of SMK Negeri 1 Mojosongo, so that it can increase the motivation and interest of Gen Z in the waste management sector through interesting activities. The existing activity method is carried out by holding counseling or socialization and training. This community service activity was attended by 28 students of SMK Negeri 1 Mojosongo, Boyolali, Department of Plant Production Agribusiness. The participants were given material as the first stage of counseling or socialization, then continued with the second stage, namely training with the practice of making calcium fertilizer. The provision of a questionnaire to improve student abilities was carried out to measure the increase in student understanding regarding the manufacture of calcium fertilizer. The results obtained showed an increase in student understanding of 64.22%.